Topological indices and QSPR modeling of some novel drugs used in the cancer treatment. Issue 24 (8th September 2021) - Havare, Özge Çolakoğlu
Abstract: Cancer is a deadly disease. There is no drug yet for the treatment of some types of cancer. New drug trials are being conducted to treat this disease. One of them is HDAC‐based multi‐target drugs. Topological indices (TIs) are the numerical descriptors of a molecular structure obtained by the molecular graph. TIs can be used in the structure–property relationship (QSPR) and structure–activity relationship studies to provide information about the physicochemical properties and biological properties of molecules. In this paper, vorinostat, tucidinostat, triciferol, and CUDC‐101 and CUDC‐907, which are seen as an important light in cancer treatment, are studied. M‐polynomials based on degree and NM‐polynomials based on the sum of degrees of neighboring vertices for chemical graphs of these drugs are calculated. By using these polynomials, many TIs that depend on the degree and the sum of neighboring degrees are obtained. Moreover, The QSPR models are designed using these TIs to estimate some physicochemical properties of these drugs. The QSPR studies are obtained using the curvilinear regression method. Abstract : Topological indices (TIs) can be used to predict the physicochemical properties of molecules in chemical graph theory. In this article, M‐polynomials and NM‐polynomials of vorinostat, tucidinostat, triciferol, CUDC‐101, and CUDC‐907 drugs, which are seen as an important light in cancer treatment, are computed. By using these polynomials, various TIs of these drugs are obtained. This article shows that between physicochemical properties of these drugs and various TIs are highly correlated.